THE USE OF HEALTH SAVING EDUCATIONAL TECHNOLOGIES IN PROFESSIONAL ACTIVITIES OF DOCTOR OF DOMESTIC - Yemets, A. (World of Medicine and Biology, 2018)
Analysis of research in the training of specialists in family medicine is based on innovative approaches. In too time of research of problem of strengthening of health, forming for them cultures of health bymeans of health saving educational technologies testifies to the attempts of scientists to ground the theoretical, methodological and methodical measures of a certain phenomenon, define the concept of terminological spectrum of this problem, to find out ways of her decision in modern sociocultural terms.